Where to Step? Contributions of Stance Leg Muscle Spindle Afference to Planning of Mediolateral Foot Placement for Balance Control in Young and Old Adults - Arvin, Mina; Hoozemans, Marco J. M.; Pijnappels, Mirjam; Duysens, Jacques; Verschueren, Sabine M.; van Dieën, Jaap H. (Frontiers in Physiology, 2018)
Stable gait requires active control of the mediolateral kinematics of the body center of mass (CoM) and the base of support (BoS) in relation to each other. Stance leg hip abductor (HA) muscle spindle afference may be used to guide contralateral swing foot placement and adequately position the BoS in relation to the CoM. We studied the role of HA spindle afference in control of mediolateral gait stability in young and older adults by means of muscle vibration. Healthy young (n=12) and older (age > 65 yrs, n=18) adults walked on a treadmill at their preferred speed. In unperturbed trials, individual linear models using each subject’s body CoM position and velocity at mid-swing as inputs accurately predicted foot placement at the end of the swing phase in the young (mean R2 = 0.73 (SD 0.11)), but less so in the older adults (mean R2 = 0.60 (SD 0.14)). In vibration trials, HA afferrence was perturbed either left or right by vibration (90 Hz) in a random selection of 40% of the stance phases. After vibrated stance phases, but not after unvibrated stance phases in the same trials, the foot was placed significantly more inward than predicted by invidual models for unperturbed gait. The effect of vibration was stronger in young adults, suggesting that older adults rely less on HA spindle afference. These results show that HA spindle afference in the stance phase of gait contributes to the control of subsequent mediolateral foot placement in relation to the kinematics of the center of mass, to stabilize gait in the mediolateral direction and that this pocess is impaired in older adults.